Fear, paranoia, McCarthyism and the XXI century: using the 22th episode of twilight zone in classroom. - Santos, Rodrigo Otávio dos (História: Questões e Debates, 2018)
This paper pretends to offer to history teachers in high school concerns about the Cold War and the McCarthy era, as well as about the problems in Brazil and the world in XXI century or the use of it in classroom form the 22th episode of the tv show Twilight Zone. For that, we will discuss television itself as a communication media, its use in classroom and pros and cons in didactic use. We also write about the Mccarthy era in USA and the reflexes of it in culture. After that, we will write about the episode, showing the focus points in which teachers can pay more attention. At last, we will indicate to the teacher ways of using this episode in classroom.